Analisis pengaruh kualitas bahan baku dan proses produksi terhadap kualitas produk pada PT. Berkah Anugerah Inti Semesta - Majid, Muhammad Naufal; Saifuddin, Joumil Aidil (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study analyzes the effect of raw material quality and production processes on product quality at PT Berkah Anugerah Inti Semesta. The background of this study is the importance of maintaining product quality to improve competitiveness in the global market. Using a quantitative approach, data was collected through questionnaires distributed to 30 employees involved in the production process and raw material management. The results show that the quality of raw materials and production processes significantly affect product quality, with regression coefficients of 0.144 and 0.657, respectively. The recommendation for future research is to explore other factors that contribute to product quality. The findings emphasize the need for a holistic approach in quality management.